Model Sistem Dinamik untuk Strategi Pasokan Air Berkelanjutan di Area Sentul City - Danang Aria Pranedya Baskoro; Atep Hermawan; Tri Permadi (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2021)
Good management of water resources is a requirement for an area that has a high population development. Sentul City, which is an independent city in Bogor Regency which has a high population, is in an area that lacks water, because of this Sentul City requires infrastructure and policies that are able to ensure the availability of water for its residents. One of the paradigms of water management in urban areas is a water sensitive city. One of the steps in this paradigm is wastewater management and rainwater harvesting. The dynamic system modelling method is used to predict the impact of implementing several policies that will be taken to manage water resources. The objectives of this study are to build dynamic models to predict water supply and demand and to analyze policies for wastewater management and rainwater harvesting. Sentul City water demand is estimated will reach 122 105 000 m3 and a water crisis will occur in 2027. The wastewater recycle policy can inhibit the water crisis until 2030 and the negative water balance will last until 2040. Combining wastewater recycle and rainwater harvesting can increase water availability by 240% and prevent a water crisis.